(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Substantial increases in global energy consumption and depletion o f fossil energy resources demand for development o f alternative energy resources. The more significant part (74%) of renewable energy sources has been planned for biomass energy in European Union. Substitution of fossil feedstocks for energy and materials by biomass is important measure for GHG emission mitigation. Development o f biodegradable polymers, construction materials and organic fertilizers from biomass let us challenge economy to a more sustainable way.Naturally biomass is material of low density therefore new mobile equipment and technologies for biomass communition and densification have to be worked out. Compacted biomass has higher volumetric energy density and can be easier transported and stored than natural biomass.Wheat straw biomass densification experiments have been carried out. Chopped straw with moisture content less 10% has been used for densification. Fine chopping significantly influence compacting density and is more preferable as heating. Cold compacting of fine chopped wheat stalk material with addition o f molasses more than 9% and sapropel more than 18% provide density lg/cm3 without any heating. The same density (Ig/cm3) has been obtained in compacting o f straw and peat composition. These results are useful for briquetting technology design.